2010
DOI: 10.1007/s00464-010-1317-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of natural orifice transluminal endoscopic surgery and endoscopy shows similar hemodynamic impact in a porcine model

Abstract: Heart rate and DBP were similar for NOTES and endoscopy. The differences seen in a previous trial comparing NOTES and laparoscopy were not duplicated. The initial DBP increased for the endoscopy and diagnostic NOTES animals. Differences in end-tidal CO(2) were encountered again during the shortened laparoscopy segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Whereas similar complication rates between groups were reported, the NOTES group had a lower need for postoperative analgesia, a faster recovery, and better cosmetic results compared to the laparoscopy group. Controlled studies comparing transgastric NOTES to laparoscopy in pigs suggest that viewing, cardiopulmonary and immunologic effects are similar …”
mentioning
confidence: 99%
“…Whereas similar complication rates between groups were reported, the NOTES group had a lower need for postoperative analgesia, a faster recovery, and better cosmetic results compared to the laparoscopy group. Controlled studies comparing transgastric NOTES to laparoscopy in pigs suggest that viewing, cardiopulmonary and immunologic effects are similar …”
mentioning
confidence: 99%
“…It should however be noted that air insufflation rather than CO 2 was used for all NOTES procedures published by Bingener's group. [13][14][15]26 Von Delius et al 22 found differences in hemodynamic responses for CO 2 versus air insufflation and as such it must be considered that the . Furthermore, the choice of air insufflation is contrary to NOSCAR recommendations, which promote the use of CO 2 as the insufflation gas of choice, similar to laparoscopy, as it is noncombustible and highly dissolvable in water, theoretically minimizing risk of air embolus.…”
Section: Discussionmentioning
confidence: 99%
“…They also found NOTES to be less detrimental to cardiopulmonary parameters compared with laparoscopy, with greater decrease in oxygen saturation levels and pH as well as greater increase in heart rate for laparoscopy than for NOTES. 14 This, however, was not reproduced in their more recent 2011 trial 15 comparing NOTES transgastric peritoneoscopy, laparoscopic mesh placement, and NOTES mesh placement in 37 randomized porcine subjects, which found no difference in heart rate, blood pressure, or arterial blood gas measurements throughout the procedures. Trunzo et al, 12 comparing NOTES and laparoscopy for both CO 2 and air insufflation groups for each procedure in 41 trial pigs and 10 controls …”
Section: Notes Versus Laparoscopic Surgerymentioning
confidence: 99%
“…In reply, a modest number of studies concerning mostly the immunologic response as well as the intraperitoneal pressure fluctuations were published, with even fewer reports submitted on cardiovascular effects during NOTES. [ 7 8 9 ]…”
Section: Discussionmentioning
confidence: 99%